Efforts to reduce crop loss from parasitic witchweed attacking Afica's staple crops. - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2011)
A meeting of researchers, farmers and other stake holder to combine technologies available in fighting the parasitic weed that is up to 80%loses in yield on farmers filed across sub-Saharan africa